2021
DOI: 10.1177/0361684321992046
|View full text |Cite
|
Sign up to set email alerts
|

Political Ideology Modifies the Effect of Glass Cliff Candidacies on Election Outcomes for Women in American State Legislative Races (2011–2016)

Abstract: Research on glass cliff political candidacies shows that compared to men, women are more likely to run for office in districts where they are likely to lose. We examined if party differences in whether female candidates face these worse conditions in the United States could account for persistent and growing party and state variation in women’s representation. Using election data from 2011 to 2016, we compared Republican versus Democratic candidacies at the state legislative level. We found that women in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
(91 reference statements)
1
9
0
Order By: Relevance
“…2Two studies (Bowles, 2013; Robinson, 2019) reported a mix of continuous and dichotomous predictor variables. In these cases, we only used the continuous variables.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2Two studies (Bowles, 2013; Robinson, 2019) reported a mix of continuous and dichotomous predictor variables. In these cases, we only used the continuous variables.…”
mentioning
confidence: 99%
“…10Because of large variability in sample sizes, three effect sizes (Funk, 2017; Robinson, 2019; Sun, Zhu, & Ye, 2015) had more weight in the analysis than all of the other studies combined. A sensitivity analysis excluding these three studies did not substantially change the summary effect size ( g = .07) or the results of the moderation analyses.…”
mentioning
confidence: 99%
“…If two people face similar work and life demands, the one with fewer resources experiences more work-life conflict (Kossek and Lee 2017) but also might benefit more from work-life enrichment. For example, people with conservative views generally subscribe to more traditional gender roles, in which men are breadwinners and leaders and women are caretakers and homemakers (Robinson et al 2021). If conservative working women face the same work demands as socially liberal working women, but they have more constrained life-based resources because they shoulder more responsibility at home, they may experience more work-life conflict than their liberal counterparts (Geist 2005).…”
Section: Role Of Consumers' Work-life Circumstancesmentioning
confidence: 99%
“…Female respondents to the survey seem to recognize this potential benefit in the CAE certification program. The results underscore the need to understand that female association professionals view the certification as a means of breaking through the glass ceiling (Ayub et al, 2019;Mungaray & Curtin, 2021;Parmer, 2021) and avoiding the glass cliff (Morgenroth et al, 2020;Rhode, 2017;Robinson et al, 2021;Ryan & Haslam, 2005) The CAE certification can provide employers an opportunity to offer advancement options that seem to elude many women in the current professional environment.…”
Section: Discussion Of the Findingsmentioning
confidence: 95%
“…Women in senior leadership positions also face a "glass cliff" that makes their grasp on management positions much more tenuous than their male counterparts. The glass cliff represents the concept of women and minorities advancing to leadership positions with a disproportionate chance of failure (Morgenroth et al, 2020;Rhode, 2017;Robinson et al, 2021;Ryan & Haslam, 2005). Many times, the perilous nature of the position is due to the woman appointed during a time of crisis (Glass & Cook, 2020;Morgenroth et al, 2020;Ryan & Haslam, 2005).…”
Section: Barriers To Leadership For Womenmentioning
confidence: 99%